Teachers’ interventions against the behaviors of children with intellectual disability - Mumpuniarti Mumpuniarti; Wening Prabawati; Hermanto Hermanto; Sukinah Sukinah; Ade Putri Sarwendah; Suparno Suparno (Journal of Education and Learning (EduLearn), 2023)
Teachers’ interventions against the behaviors of students with intellectual disability (ID) are urgent for their instructional strategies in the classroom. There were 42 teachers of children with ID given a questionnaire via Google Forms. The questions posed concerned the antecedents of the behavior problems in students with ID, the forms of the behavior problems, teachers’ measures, post-intervention conditions, and suggestions for parents. The strongest trigger of behavior problems found was the teacher’s direction for a task, in which task refusal. In response to the task refusal behavior, the teacher took a measure by calming the students down and resulted in the students turning calm. This predictor of the teacher’s intervention can be applied as a basis for parents’ participation in collaboration to overcome behavior problems in students with ID. The teachers’ interventions against behavior problems in students with ID took the form of measures that were of the fading and prompting nature as well as the form of verbal diversion. The teachers’ interventions above mentioned can be used as predictors as they are relevant to the antecedents of the behavior problems of the students with ID, the forms of the behavior problems, and the concequences the teachers should follow.